Taxonomic note on Abax contractus (Heer, 1841) and description of A. parallelepipedus ligurinus n. subsp. (Coleoptera, Carabidae, Pterostichini) - Zanella, Lorenzo (Zootaxa, 2017)
The syntype of Pterostichus contractus Heer, 1841 was examined and its taxonomical position was revised accordingly. The historical interpretation of this taxon as a subspecies of Abax parallelepipedus localized in the area between the Maritime-Ligurian Alps and the northern Apennines is rebutted. The taxon is raised to species level under the name Abax contractus (Heer, 1841), as a senior synonym of Abax continuus Ganglbauer, 1891 n. syn. and A. hypocrita Roubal, 1937 n. syn. The subspecies of Abax parallelepipedus previously reported as subsp. contractus Heer, 1841 is re-described under the name Abax parallelepipedus ligurinus n. subsp.